2007
DOI: 10.4070/kcj.2007.37.9.419
|View full text |Cite
|
Sign up to set email alerts
|

Lesion Location: Its Impacts on the Procedural and Postprocedural Outcomes of Unprotected Left Main Coronary Stenting

Abstract: Background and Objectives:Percutaneous coronary intervention (PCI) for unprotected left main coronary artery (LMCA) stenosis is a promising technique in the drug-eluting stent era. However, there is a lack of data as to the impact of the lesion location in the LMCA on the procedural and postprocedural outcomes. The aim of this study is to evaluate the effect of lesion location on the procedural and postprocedural outcomes. Subjects and Methods: From July 2003 to January 2006, we enrolled 82 patients (Males: n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Recent studies evaluating percutaneous coronary intervention (PCI) with drug-eluting stent (DES) for left main (LM) disease have shown promising results. 1) 2) However, the decision to intervene the jailed left circumflex coronary artery (LCX) after an LM stent extending into the left anterior descending coronary artery (LAD) is difficult in some cases if based on angiogram alone. Previous studies suggested that measurement of fractional flow reserve (FFR) across jailed side branch lesions prevents unnecessary complex interventions in bifurcation lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies evaluating percutaneous coronary intervention (PCI) with drug-eluting stent (DES) for left main (LM) disease have shown promising results. 1) 2) However, the decision to intervene the jailed left circumflex coronary artery (LCX) after an LM stent extending into the left anterior descending coronary artery (LAD) is difficult in some cases if based on angiogram alone. Previous studies suggested that measurement of fractional flow reserve (FFR) across jailed side branch lesions prevents unnecessary complex interventions in bifurcation lesions.…”
Section: Introductionmentioning
confidence: 99%